(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Syamsuardi, Nurainas, Taufiq A, Harmawan T, Suwardi AB. 2021. Aneuk Jamee traditional foods in the South Aceh District, Indonesia. Biodiversitas 23: 443-454. The traditional foods of the Aneuk Jamee Tribe have a long history and unique traditions passed down for thousands of years. However, a lack of information about indigenous and traditional foods of the Aneuk Jamee Tribe will lead to a decline in local knowledge of traditional foods, particularly among the younger generation. Therefore, this study aimed to investigate the variety of Aneuk Jamee traditional foods in the South Aceh District of Indonesia. The study was conducted in South Aceh, Indonesia, Labuhan Haji Timur, Kota Bahagia, and Kluet Selatan Sub-districts. The study involved 90 respondents (30 from each sub-district) chosen at random. The interview was conducted using a questionnaire covering the respondents’ backgrounds, traditional food names, food composition, mode of preparation, and uses. As a result, 52 Aneuk Jamee’s traditional foods were identified from three sub-districts of South Aceh District, including 41 types of traditional cuisine and 11 types of traditional snacks. All respondents recognised Gulai ciik minyak, Gulai taleh, Gulai paku, Gulai cabadak, Gulai kabau, Gulai kambieng, Gulai ikan panjang, Gulai kitang, Kue kakareh, Limpieng sagu, and Limpieng ubi as Aneuk Jamee traditional foods. On the other hand, less than 20% of respondents were familiar with other traditional foods, such as Lamang ubi. The Aneuk Jamee Tribe has an excellent system for passing down traditional knowledge from generation to generation. Fifty-six plant species consisting of 47 genera and 28 families were used as Aneuk Jamee traditional food. The Aneuk Jamee Tribe prepares various foods from various plant species to maintain their health and contribute to household income and conservation efforts.